Evaluation of Waste Bank Management in Mojo Village, Gubeng Sub-district, Surabaya City - Auly, Ahdina Khoirunnisa’ul; Hadi Suryono; Winarko; Thohari, Imam; Laksono, Cahyo Widoko; Suharno (Jurnal Higiene Sanitasi, 2025)
Poor waste management can lead to environmental pollution. Waste banks, based on the 3R principles (reduce, reuse, recycle), are an effort to manage waste sustainably while enhancing community income. However, the effectiveness of waste bank operations is often hampered by low community participation, suboptimal operational mechanisms, and inconsistent application of standard operating procedures (SOPs). This study aimed to evaluate the management of waste banks in Mojo Urban Village, Gubeng District, Surabaya City. A cross-sectional observational method with descriptive analysis was employed. Variables assessed included waste generation, waste sources, operational mechanisms, and SOP components across seven waste banks. Data collection involved interviews and observations. Results showed the dominant waste types were plastic (1317.3 kg, average 219.55 kg), paper (1195.7 kg, average 199.28 kg), metal (217 kg, average 36.17 kg), and glass (81 kg, average 13.5 kg), with an overall average of 1.12 kg/day per neighborhood unit (RW). Waste originated entirely from residential areas. Operational mechanisms were rated 100% compliant, while SOP implementation reached 84.3%, categorized as good. It is recommended that waste bank managers conduct monthly community education sessions on waste separation and improve the implementation of two SOP components: waste collection and waste condition requirements. Strengthening these areas can further enhance the sustainability and effectiveness of waste bank management.